Kite

Written by Jerry Ratzlaff on . Posted in Plane Geometry

kiteEdge formula

\(a = \frac {p}   {2} -b   \)

\(b = \frac {p}   {2} -a   \)

Where:

\(a\) = edge

\(p\) = perimeter

\(b\) = edge

Diagonal formula

\(D1 = 2 \frac {A}   {D2} \)

\(D2 = 2 \frac {A}   {D1} \)

Where:

\(D1\) = diagonal

\(A\) = area

\(D2\) = diagonal

Perimeter formula

\(p= 2 \left( a + b   \right) \)

\(p= 2a + 2b \)

Where:

\(p\) = perimeter

\(a\) = edge

\(b\) = edge

Area formula

\(A =\frac { {D1}   {D2} }{2} \)

Where:

\(A\) = area

\(D1\) = diagonal

\(D2\) = diagonal